Revitalization and the Meaning of Space in Surabaya’s Old Town: The Rajawali – Kembang Jepun Corridor - Witjaksono, Ninditarari Salsabila; Parlindungan, Johannes; Surjono, Surjono (Fakultas Teknik Universitas Brawijaya, 2026)
Urban revitalization in historical cities usually focuses on physical upgrades and encouraging tourism, but there has not been much exploration of how these changes affect the meaning of space. This study examines how the revitalization of the Jalan Rajawali to Kembang Jepun corridor in Surabaya’s Old Town changes the feel of a place and how space is being used in that area. A qualitative descriptive approach was employed using field observation, stakeholder interviews, and spatial documentation. This research combines three analyses: typo-morphology, semiotic interpretation, and the production of a space framework to explore how physical structures, visual elements, and social practices interact after one year of revitalization. The result shows that 65% of the 136 buildings along the 1.13 km corridor experienced intervention of revitalization, affecting both heritage and nonheritage structures. Approximately 6,252 m² of land shifted from circulation and trade functions to adaptation, becoming a tourism and social public space. Although the basic morphological structure remains unchanged, facade handling, symbolic characteristics, pedestrian pathway improvements, and increased tourism activities have redefined the corridor as heritage tourism and a public space. This research shows that on Rajawali Street, it strengthens a monumental colonial identity, while on Kembang Jepun Street, it expresses a vibrant Chinatown character, creating a merging yet integrated spatial narrative. This research reveals that revitalization has a function as a process of spatial meaning production, in which physical interventions engage with collective memory and user perception. This approach combines typo-morphological and semiotic analysis to explain that heritage revitalization does not change the physical appearance of a place; it also shapes how people understand, experience, and give meaning to the space.